The Routledge companion to race and ethnicity - Caliendo, Stephen M., 1971-; McIlwain, Charlton D., 1971- (London : Routledge, 2020)
The second edition of The Routledge Companion to Race and Ethnicity offers readers a broad overview of scholarly exploration of the ways that humans have organized themselves (and have been organized) according to racial and ethnic divisions. More than 80 scholars from around the world and representing multiple academic traditions contribute entries to this accessible yet sophisticated volume that addresses contemporary issues in historical context. The first half of the book challenges readers to grapple with some of the most controversial aspects of categorization, prejudice and discrimination through focused chapters ranging from the notion of Whiteness to the supposed biological rationale for racial categorization. The second half is comprised of 70 shorter entries on specialized concepts, persons and groups that are crucial to understanding these issues. Taken as a whole, this volume provides a broad, multi-disciplinary and global overview of issues that continue to provide challenges to notions of equality and justice.
Previous edition: 2011.
Introduction 1. Origins of the Concept of Race F. Carl Walton and Stephen M. Caliendo 2. Ethnicity Vivian Ibrahim 3. Whiteness Robert Jensen 4. Colonialism/Postcolonialism William Muck 5. Race, Politics and Public Policy Charlton D. McIlwain and Stephen M. Caliendo 6. Race-based Social Movements Charlton D. McIlwain 7. Immigration Katharina Natter 8. Race, Gender and Sexuality Nina Asher 9. Race, Media and Popular Culture Stephen M. Caliendo 10. Race, Ethnicity and Globalization S. P. Udayakumar A to Z: Key Concepts in the Study of Race and Ethnicity
OCLC-licensed vendor bibliographic record.
Keywords: Race; Ethnicity; SOCIAL SCIENCE / Sociology / General